Multiply doses of FDC of rosuvastatin and ezetimibe versus rosuvastatin monotherapy in Chinese patients with hypercholesterolemia (ROSE-CH): multicenter, randomized-controlled trial - Xianyou Ji; Jinlan Xia; Hong Zhang; Changjie Ren; Guang Ma; Shenwen Fu; Jun Zhang; Ying Chen; Xuebin Han; Jianming Zhang; Zhengxu Fang; Bo Yang; et al. (Lipids in Health and Disease)
Abstract Objective Rosuvastatin plus ezetimibe improves the lipid-lowering effect through different mechanisms of action. This study intended to compare the efficacy and safety of the fixed-dose combination (FDC) of rosuvastatin/ezetimibe vs. rosuvastatin alone in hypercholesterolemia patients. Methods ROSE-CH (ROSuvastatin and Ezetimibe in Chinese Hypercholesterolemia patients) was a multicenter, randomized, double-blind, positive drug-controlled, superiority-tested phase III clinical trial; 743 patients were randomized into rosuvastatin/ezetimibe 10/10 mg, 5/10 mg, and 2.5/10 mg groups, as well as rosuvastatin 10 mg and 5 mg groups at a 1:1:1:1:1 ratio. A total of 143, 127, 263, and 137 patients had low, intermediate, high, and very-high baseline atherosclerotic cardiovascular disease (ASCVD) risks. The study period spanned from December 24, 2021, to December 6, 2022. Results Efficacy and safety assessments were conducted in 670 and 696 patients. Percentage change in low-density lipoprotein cholesterol (LDL-C) from baseline to week (W)12 was greater in the rosuvastatin/ezetimibe 10/10 mg group vs. rosuvastatin 10 mg group [least-squares means (LSmean): -51.48% vs. -42.47%], rosuvastatin/ezetimibe 5/10 group vs. rosuvastatin 5 mg group (LSmean: -50.08% vs. -40.17%), and rosuvastatin/ezetimibe 2.5/10 mg group vs. the rosuvastatin 5 mg group (LSmean: -48.47% vs. -40.17%) (all P < 0.001). The same trend was observed for the percentage change in LDL-C from baseline to W4 and W8 (all P < 0.001). In patients with baseline very high ASCVD risk, the achievement of LDL-C target at W12 was higher in rosuvastatin/ezetimibe 10/10 mg vs. rosuvastatin 10 mg groups and rosuvastatin/ezetimibe 2.5/10 mg vs. rosuvastatin 5 mg groups (both P < 0.05). The incidence of adverse events was 36.0%, 38.7%, 25.2%, 31.4%, and 38.6% in each group. Regarding serious adverse events, the incidence was 2.2%, 2.9%, 0.7%, 3.6%, and 0.7% in each group. The incidence of drug-related adverse events was relatively high, which was 26.6%, 31.4%, 18.5%, 23.6%, and 29.0% in each group, respectively, irrespective of the absence of serious drug-related adverse events. Conclusion The FDC of rosuvastatin/ezetimibe has superior LDL-C-lowering effects over rosuvastatin alone, with good safety profiles in hypercholesterolemia patients.